1993
DOI: 10.1007/bf02545342
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic modification of canola/palm oil mixtures: Effects on the fluidity of the mixture

Abstract: The bioreactor system to interesterify edible oils and fats at an ultra-micro aqueous phase of 100 ppm and less was investigated. The adsorption of lecithin, together with lipase onto a carrier, was effective for conducting the interesterifying reaction efficiently for oils and fats in micro aqueous phase.To improve the handling properties of palm oil at rather low temperature, palm oil was blended with canola or soybean oil, and then these blended oils were modified by enzymatic selective interesterification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Some examples reported recently include the transesterification of tallow with sunflower, soybean [9], rapeseed oil [10], and canolapalm oil mixtures [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples reported recently include the transesterification of tallow with sunflower, soybean [9], rapeseed oil [10], and canolapalm oil mixtures [11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some studies (KURASHIGE et al, 1993;SOARES et al, 2003) have demonstrated a good compatible of this surfactant with enzymes and successfully employed as stabilizing agent of lipase during immobilization on solid supports.…”
Section: Glycerolysis Reactions In Batch Reactormentioning
confidence: 99%
“…Blended oils are also subjected to lipase mediated interesterification reaction to get desirable characteristics (Debnath, Prakash, & Lokesh, 2011). It is reported that enzyme modification of palm oil improved the handling properties at low temperature when it was blended with canola or soybean oil (Kurashige, Matsuzaki, & Takahashi, 1993). Solid fats such as tallow and butterfat, which was interesterified with high oleic sunflower oil and soybean oil showed improved physical and thermal characteristics (Foglia, Petruso, & Feairheller, 1993).…”
Section: Introductionmentioning
confidence: 98%